O trabalho do núcleo de apoio a saúde da família (NASF) e da educação física na atenção básica: em busca de sentido - Furlan, Allana Antonello (2016)
The Nucleus of Support for Family Health (NASF) is a strong field of action in the context of Primary Care (AB) for Physical Education as well as to the other professions that compose it. It's justified the importance of trying to understand how their work process is organized, through professional experiences, to assist in the development of this proposal. Hereupon, this essy aims to describe the professional profile, understand the characteristics and the working meaning of a NASF and the Physical Education Professionals (PEF), working at the AB in the city of Maringá, from the theoretical assumptions of Logotherapy. It is a qualitative research performed with seven professionals from the same NASF and six PEF belonging to the city. The methodological instruments used were: observation, focus groups, individual interviews and documentary research. The technique employed was "Content Analysis" proposed by Bardin (1977). Two original papers make up the essay. The Logotherapy theory from Viktor Emil Frankl about the meaning of work to support the discussions was employed. The first paper aimed to describe the profile and characteristics of of a NASF?s working process and the PEF working in primary care in the city of Maringá. From the analysis of the material emerged 10 categories that have been grouped into two topics for discussion: 1) The working process of a NASF team: implementation facts and current organizational forms 2) the job characteristic of the physical education professional. The results showed that the studied teams participated in the construction of the work process facing challenges in implementation, such as the unfamiliarity of a NASF function, the resistance of some EqSF and the management mismatch with NASF guidelines. It was found the differentiation in PEF pay and work hours in relation to other categories. Despite the adversities, PEF and NASF developed organizational models to viii perform their work. The second paper aimed to understand the work meaning for a NASF and for the PEF working at the AB in the city of Maringá from the Logotherapy theoretical assumptions. The analysis of the material generated 13 categories that were discussed in two topics: 1) The work features in NASF that gives meaning to the lives of professionals: a reflection from the Logotherapy theory; and 2) the comprehension of the meaning of work in the NASF for physical education professional active on the job and Logotherapy contributions. The main factors reported, that attache meaning to the work in NASF, are linked to the contact and relationship with the community served and is related to the professional motivation and personal fulfillment. As well as in other areas, which has sought in the Logotherapy contributions to the work environment, it is hoped that this theory may also contribute to the progress of physical education in health care and to the advance of the NASF proposal.